ANALISIS WACANA DALAM KULIAH UMUM DEDI MULYADI DI UNIVERSITAS ISLAM NEGERI SUNAN GUNUNG DJATI BANDUNG - Apiyudin, Arsalan Dzakwan; Fauziah , Meli (Universitas Hamzanwadi, 2026)
This study aims to describe the forms and types of code-switching and analyze their social functions in a public lecture delivered by Dedi Mulyadi at UIN Bandung. The research scope covers internal code-switching, code-mixing, social context, and rhetorical functions within the lecture. A qualitative approach was employed through literature review and direct observation, drawing on theories from Rahardi, Wardhaugh, Holmes, and Chaer & Agustina. Data were collected through direct observation, documenting 10 instances of code-switching and 5 instances of code-mixing in the speaker’s expressions . The findings indicate that code-switching serves to emphasize meaning, create humor, and reinforce the speaker’s Sundanese cultural identity. Notably, several Sundanese philosophical expressions—such as “Rama, resi, ratu, gunung kudu awian” and “Kudu balik ka dirina, mulang ka asalna”—highlight the symbolic role of language in forming emotional connections with the audience. This research demonstrates that code-switching is not merely a linguistic phenomenon but also a cultural communication strategy within academic settings.